Sistem Pendukung Keputusan Penerima Program Keluarga Harapan (PKH) dengan Metode Simple Additive Weighting (SAW) - Lisa Riyanti; Gunawan Ali; Amril (Rektorat Universitas Putra Indonesia YPTK Padang, 2022)
The Family Hope Program (PKH) is a program for providing conditional assistance to Beneficiary Families (KPM) who are designated as PKH beneficiary families. This PKH program provides cash assistance to very poor households (RSTM) that meet the requirements and are related to efforts to improve the quality of life in the fields of education and health. However, in the management of PKH data, several problems were found, such as in the distribution aspect. In the distribution aspect, it is often found that the distribution of PKH is not right on target or the distribution of PKH to families who do not deserve this PKH program. Various efforts have been made to overcome these problems, one of which is by making a decision support system using the Simple Additive Weighting (SAW) method. The decision support system with the SAW method can provide recommendations or support to determine the right PKH recipients. The SAW method is a weighted addition method, which is looking for a weighted sum of ratings for each alternative on all attributes/criteria. The result of the total score obtained for an alternative is by adding up all the multiplication results between the ratings compared across attributes and the weight of each attribute. The Decision Support System for determining PKH recipients using the SAW method provides the right results. The alternative is the highest order to have a good score on the criteria that have the highest importance and is very precise with real data so that the distribution of PKH is right on target.